Bioinspired cementitious-polymer composite for increased energy absorption - Painter T. Trevor (EDP Sciences, 2021)
Preliminary results are presented on the energy absorbing characteristics of a cementitious-polymer architecture bioinspired by the organic-inorganic composite structure of nacre. The proposed bioinspired architecture consists of an open cell, platelet-shaped 3D-printed thermoplastic lattice filled with high performance cementitious paste. The hypothesis is that, similar to nacre, the platelet arrangement and differences in mechanical properties of the thermoplastic lattice and cementitious platelets would result in increased energy absorption. Initial laboratory scale investigations were performed using notched beam samples subjected to static three-point bending. Stereo-digital image correlation was used to track global strain displacement field and Hillerborg’s method was used to estimate the total fracture energy. The results indicate that this “brick-and-mortar” hierarchy can increase the energy absorbing capacity of the composite by upwards of 2490% compared with the benchmark cementitious specimen. The load-deformation behaviour and total fracture energy of the bioinspired composite were found to be influenced by the platelet arrangement and size and the lattice thickness.